Deep Learning Techniques to Evaluate Changes in Walkability in Downtown Orlando via Street Panorama Imagery - Chia-Yuan Yu (Findings)
This study examines changes in walkability in downtown Orlando from 2018 to 2021 using Google Street View data and deep learning techniques. The results showed significant enhancements in greenery, increasing from 7.2% to 11.9%, and sidewalk pavement coverage, rising from 10.5% to 15.8%. However, outdoor openness decreased from 21.3% to 18.7% due to new high-rise buildings. Variations were evident between the east and west sides of downtown, divided by Interstate-4, with the east side having higher sidewalk pavement coverage and greenery.